Relative abundance and habitat selection of the montane guinea pig Cavia tschudii in a wetland at coastal desert with comments on its predators - Quispe-López, Manuel; Barreda, Sue; Marcelo-Carranza, Diego; Pacheco, Víctor; Aponte, Héctor; Ramirez, Dámaso W. (THERYA, 2021)
Cavia tschudii inhabits coastal and Andean wetlands where it is important prey for medium carnivores, but its habitat selection and its role in the wetlands are unknown. In order to reduce this lack of knowledge, we evaluated changes in the abundance for two seasons and the habitat selection of C. tschudii in a wetland on the central coast of Peru. Additionally, we report information on their movement distances and provide comments on their predators. We carried out six evaluations during the autumn and spring of 2019, with nine grids in three plant communities: grassland, bulrush community, and cattail community. Each captured individual was marked with a numbered ear tag. We compared the relative abundance between seasons using the Mann-Whitney U test, and calculated the relative abundance per evaluated month and carried out regressions to model its behavior. The use/availability of habitat was evaluated with the Chi-square test together with Bonferroni confidence intervals to show habitat selection. Finally, we estimate the mean maximum distance moved (MMDM) of recaptured individuals. The results show significant differences between the seasons, with higher relative abundance in autumn. The relative abundance showed a peak in April, from which the values decrease. Likewise, we found significant differences in habitat selection, showing positive selection for the cattail community, neutral selection for the bulrush community, and negative selection for the grassland. The MMDM was 36.5 Â± 15.7 m. We report a decrease in the relative abundance of C. tschudii, possibly related to seasonal changes in habitat quality or to the presence of predators. The peak of abundance in mid-autumn and the apparent decrease in the population until late spring resembles the annual dynamics reported for C. aperea. It is also confirmed that C. tschudii, like other Cavia, select environments with greater plant coverage, possibly as an anti-predation strategy. We report dogs predating C. tschudii and provide a list of other potential predators. This study increases the information on C. tschudii in coastal wetlands and gives a first approach to the necessary knowledge for its management and conservation within these fragile ecosystems.